Repercussions of FUNDEF/FUNDEB on Initial Remuneration of Teachers from Pará's State Public School System - Fabrício Aarão Freire Carvalho (Arizona State University, 2015)
This article aims to analyze the repercussions of FUNDEF/FUNDEB at initial remuneration of education professionals from Pará's State public school system between 1996 and 2009. It represents a public policy analysis, concentrating its focus on the examination from the implication of funds policy for teaching's effective valorization in the State. The research came to the conclusion that, concerning payment, these professionals received a value under the minimum wage nationally established. The initial remuneration of the state's teachers is low, both in relation to professionals graduated from high school, as in relation to higher education professions with greater social prestige and the same working hours. In general, the teachers, even receiving the FUNDEF/FUNDEB bonus, did not manage to match their pay with those professionals.